Praktik MSDM sebagai Determinan Kinerja Organisasi dengan Mediasi Manajemen Pengetahuan - Moh. Muzamil; Meirani Harsasi; Faridah Iriani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Human resources are the most vital resources for the success of an organization, including in higher education organizations. The application of good human resource management (HRM) practices leads to efforts to share knowledge among members of the organization. This study seeks to prove the effect of good HRM practices on organizational performance mediated by knowledge management. This research was conducted at a public university with the number of samples collected as many as 1,014. By using SEM PLS, this study succeeded in proving that good HRM practices have a positive effect on knowledge management. Another result is the positive influence of knowledge management on organizational performance, as well as the positive influence of HRM on organizational performance.